2012
DOI: 10.4103/0019-5413.90427
|View full text |Cite
|
Sign up to set email alerts
|

Two stage procedure for neglected transscaphoid perilunate dislocation

Abstract: We report a two-staged surgical procedure for neglected 3 month old volar transscaphoid, transcapitate perilunate fracture dislocation wrist in an 18 year old right handed male student. The lunate with proximal scaphoid and proximal capitate maintained its articulation with distal end radius while the rest of carpal bones had dislocated volarly. In the first stage, bilateral uniplanar wrist distractor was applied with the aim of stretching soft tissue. In the next stage open reduction and internal fixation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…7 In patients where open reduction is not successful or those presenting after 2 months, a reconstructive or salvage procedure is generally required. 3 Patients presenting late with VPLDs have more chances of developing complex regional pain syndrome (CRPS) in the post-operative period. CRPS occurs due to central and peripheral nociceptive sensitisation, altered sympathetic function, inflammatory and immune related factors, brain changes, and psychological factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 In patients where open reduction is not successful or those presenting after 2 months, a reconstructive or salvage procedure is generally required. 3 Patients presenting late with VPLDs have more chances of developing complex regional pain syndrome (CRPS) in the post-operative period. CRPS occurs due to central and peripheral nociceptive sensitisation, altered sympathetic function, inflammatory and immune related factors, brain changes, and psychological factors.…”
Section: Discussionmentioning
confidence: 99%
“…2 Patients presenting late are particularly difficult to manage due to soft tissue contractures and increased chances of 1) avascular necrosis of scaphoid and lunate, 2) tractional injury to neurovascular structures, 3) wrist stiffness, and 4) complex regional pain syndrome (CRPS). 3 We, through this case report, aim to highlight the problems faced in managing neglected VPLDs and importance of prompt restoration of intercarpal alignment in such injuries to prevent complications. We also state that early recognition and treatment improves patient outcomes in CRPS.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,10) Other authors have reported a twostage open reduction and internal fixation protocol that involves gradual distraction. 4,5) However, Inoue and Shionoya 11) have reported that open reduction for cases neglected more than two months carries an unfavourable outcome. Komurcu et al 3) reported that results of delayed cases managed with ORIF were inferior to those of the acute cases even though the delay in all cases in their series was less than 45 days.…”
Section: Discussionmentioning
confidence: 99%
“…2) But more recently, a two-stage reduction protocol was reported by some authors. 4,5) Scaphoid excision plus four corner fusion (SE4CF) has been used successfully for the treatment of Scapholunate advanced collapse (SLAC) and Scaphoid nonunion advanced collapse (SNAC) which are neglected carpal injuries that progressively result in a dissociative type of carpal instability. 6,7) Our hypothesis was that SE4CF could be used to treat neglected perilunate dislocations with good pain relief and good hand function.…”
Section: Introductionmentioning
confidence: 99%
“…2 Additionally, several recent cases of misdiagnosis of perilunate dislocation have been reported, [3][4][5] highlighting the fact that this diagnosis is still being missed. Owing to the rarity of perilunate dislocation, the radiological signs are often not recognised by primary care doctors, including emergency physicians.…”
Section: Why Is Perilunate Dislocation Missed?mentioning
confidence: 99%